2024
DOI: 10.7759/cureus.53292
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Suspended Particulate Matter and the Prevalence of Allergic Conjunctivitis in Japan

Tatsuya Mimura,
Takamichi Ichinose,
Ken-ichiro Inoue
et al.

Abstract: BackgroundThis study aimed to examine the association of suspended particulate matter (SPM) with outpatient attendance for allergic conjunctivitis. MethodologyThe information on air pollution, encompassing total hydrocarbons, non-methane hydrocarbons, methane, carbon monoxide, nitrogen oxide, nitric oxide, oxidants, and SPM alongside data concerning daily weather conditions such as temperature, wind speed, and humidity, was gathered. Subsequently, the weekly mean values for outpatient visits, air pollution, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…PM2.5, a critical element of atmospheric pollution, can attack a variety of different organs in the body [25]. In particular, eye epithelial cells that are subject to direct airborne contact with pollutants may become more susceptible to inflammation [26,27]. As we previously showed that PM induces inflammation [28], PM was also thought to be involved in inducing inflammation in the cornea.…”
Section: Discussionmentioning
confidence: 94%
“…PM2.5, a critical element of atmospheric pollution, can attack a variety of different organs in the body [25]. In particular, eye epithelial cells that are subject to direct airborne contact with pollutants may become more susceptible to inflammation [26,27]. As we previously showed that PM induces inflammation [28], PM was also thought to be involved in inducing inflammation in the cornea.…”
Section: Discussionmentioning
confidence: 94%